2022
DOI: 10.1016/j.jes.2021.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of PM2.5 pollution during COVID-19 pandemic in Guangzhou, China

Abstract: The COVID-19 pandemic has raised awareness about various environmental issues, including PM 2.5 pollution. Here, PM 2.5 pollution during the COVID-19 lockdown was traced and analyzed to clarify the sources and factors influencing PM 2.5 in Guangzhou, with an emphasis on heavy pollution. The lockdown led to large reductions in industrial and traffic emissions, which significantly reduced PM 2.5 concentrations in Guangzho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…However, the emission benefit from public buses in terms of NO and CO 2 may be uncertain when the bus occupancy rates are low, as observed in Taichung City buses. Although many recent studies showed improved ambient air quality, a positive environmental implication, due to restricted mobility during the pandemic [ 9 , 15 17 , 19 ], our analysis of tailpipe emissions per PKT of buses suggested that the benefit of public buses in terms of NO and CO 2 emissions per PKT over private modes of transportation became doubtful in the context of the COVID-19 pandemic. In other words, public bus transit systems can be less efficient in terms of emissions per PKT than private transport modes in the changing scenario due to the COVID-19 pandemic if appropriate measures are not adopted to increase bus usage.…”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…However, the emission benefit from public buses in terms of NO and CO 2 may be uncertain when the bus occupancy rates are low, as observed in Taichung City buses. Although many recent studies showed improved ambient air quality, a positive environmental implication, due to restricted mobility during the pandemic [ 9 , 15 17 , 19 ], our analysis of tailpipe emissions per PKT of buses suggested that the benefit of public buses in terms of NO and CO 2 emissions per PKT over private modes of transportation became doubtful in the context of the COVID-19 pandemic. In other words, public bus transit systems can be less efficient in terms of emissions per PKT than private transport modes in the changing scenario due to the COVID-19 pandemic if appropriate measures are not adopted to increase bus usage.…”
Section: Resultsmentioning
confidence: 66%
“…With the onset of the novel coronavirus disease (COVID- 19), several countries around the globe have been imposing curtailments on outdoor movement and activities of people in an effort to keep the pandemic from further spreading. The restrictions include lockdowns and the requirement to maintain social distancing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, during the COVID-19 blockade, severe haze still occurred in northern China due to high relative humidity and poor air [47]. Other factors such as transportation and secondary pollution offset the reduction of PM 2.5 concentration [48].…”
Section: Population Exposure Risks Of Pm25mentioning
confidence: 99%
“…To reduce severe air pollution, the local government has made enormous efforts to reduce PM 2.5 concentrations since 2013. Through strict control measures, the annual average PM 2.5 concentrations in Guangzhou decreased continuously from 52 μg/m 3 in 2013 to 23 μg/m 3 in 2020 (Wen et al., 2022). At the same time, O 3 concentration displayed an increasing trend and appeared as the dominant pollutant in Guangzhou (Gong et al., 2022; Wang, Guo, et al., 2019).…”
Section: Introductionmentioning
confidence: 99%